(untitled) (Research, Society and Development, 2025)
The purpose of this research project was to analyze the relation between self-efficiency and the academic performance in university students. The sample was N= 831.Two scales were used: of Scholz et al. (2002) Perceived Self-efficiency Scale and Blanco et al. (2011) Academic Behavior in Self-efficiency (EACA in Spanish). The results indicate that the General Self-efficiency correlated significantly with the university weighted average. Moreover, the scores correlated significantly and positively with the EACA sub-scales, especially with the Communication sub-scale. The Communication dimension correlated positively with all the academic performance indicators. The third dimension, Excellency, correlated with the simple university average. The three sub-scales correlated significantly and positively with the General Self-efficiency Scale.